Sensory evaluation of the wine grape Isabella (Vitis labrusca L.) hand crafted - Almanza-Merchán, Pedro José; Reyes-M., Andrea Johana; Ayala, Marco Luis; Balaguera-L., William; Serrano-Cely, Pablo Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The production and consumption of wine in Colombia have increased over the last decade, especially with the red wines which are preferred by Colombians. Spite the few organoleptic characteristics of the grape Isabella (Vitis Iabrusca L.), it possesses intense flavors and aromas, plus its low sugar content and high concentration of acids, gives it the potential to be used in winemaking. The parameters involved in the sensory evaluation of the wines are the color, aroma and flavor and become sensations perceived in different areas of the tongue. The combination of these causes’s sensations are called wine texture. Sensory analysis of wines through tastings gives rise to a description, that although subjective, generates some impact on the market position ofthis drink. Descriptive tests are the most common and can express the different sensations of wine labeling them by a scale. The aim of this study was to evaluate the organoleptic quality through blind tasting, the artisan wine grape Isabella (Vitis Iabrusca L). We valued three crafted wines, two of them produced in the Pedagogical and Technological University of Colombia, and a third from the town of Cerrito, Valle del Cauca. The panel conformed by 20 tasters evaluated the wines according to the parameters set by the profile sheet given by the International Competition of Wines and Spirits (CINVE). The results showed significant differences between the Paradise wine Portal and the Semi-dry and semi-sweet UPTC wines. The results suggest that the Semi-dry wine obtained the lowest score ranking, as the best sensorial level. The Uptc wines obtained the lowest score, classified as the best in the sensory study.